Book Reviews. Issue 1 (1st April 2017) - Madhavan, Arya; Nair, Sreenath
The Taste of British South Asian Theatres: Aesthetics and Production, Chandrika Patel (2015)Lulu Publishing Services, 252 pp., ISBN: 978-1-4834-3340-0, p/bk, £17.99Stanislavsky and Yoga, Sergei Tcherkasski (2016)Routledge, 125 pp., ISBN: 978-1-138-95409-0, p/bk, £14.26